Judicial decision-making a survey of the experimental evidence - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2022)
Judges are human beings. Is their behavior therefore subject to the same effects that psychology and behavioral economics have documented for convenience samples, like university students? Does that fact that they decide on behalf of third parties moderate their behavior? In which ways does the need matter to find a solution when the evidence is inconclusive and contested? How do the multiple institutional safeguards resulting from procedural law, and the ways how the parties use it, affect judicial decision-making? Many of these questions have been put to the experimental test. The paper provides a systematic overview of the rich evidence, points out gaps that still exist, and discusses methodological challenges.
hdl:21.11116/0000-000A-E4EF-8
Keywords: K10; K13; K14; 330; judicial decision-making; bias; heuristic; attitudinal model; ambiguity; parallel con-straint satisfaction; public perception